2005
DOI: 10.1038/sj.ijo.0802994
|View full text |Cite
|
Sign up to set email alerts
|

Use of information and communication technology and prevalence of overweight and obesity among adolescents

Abstract: Overweight was associated with using information and communication technology (ICT), but only with certain forms of ICT. Increased use of ICT may be one factor explaining the increased prevalence of overweight and obesity at the population level, at least in girls. Playing digital games was not related to overweight, perhaps by virtue of game playing being less sedentary or related to a different lifestyle than viewing television and using computer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
150
5
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(173 citation statements)
references
References 48 publications
15
150
5
3
Order By: Relevance
“…Overall, our findings show that Spanish adolescents spent less time watching TV than their counterparts in Brazil 14 21 , but more time than Finish adolescents 22 . A comparison with recent results from the HELENA study of a relatively large pooled sample of European adolescents aged 12.5 to 17.5 years also suggests that Spanish adolescents may spend less time watching TV than other young Europeans 6 .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Overall, our findings show that Spanish adolescents spent less time watching TV than their counterparts in Brazil 14 21 , but more time than Finish adolescents 22 . A comparison with recent results from the HELENA study of a relatively large pooled sample of European adolescents aged 12.5 to 17.5 years also suggests that Spanish adolescents may spend less time watching TV than other young Europeans 6 .…”
Section: Discussionmentioning
confidence: 62%
“…Although results regarding the influence of age on time spent watching TV are contradictory, by contrast, almost all the aforementioned studies showed that boys usually spend more time watching TV than girls 6,14,15,16,17,18,19,20,21,22 .…”
Section: Discussionmentioning
confidence: 87%
“…For example, the amount of time spent in watching television and using electronic games is directly related to the prevalence of obesity in children and adolescents (19)(20)(21)(22)(23)(24) . Parents' BMI was the best predictor of overweight according to the case-control study among Brazilian adolescents (25) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted in older school aged children (i.e. ≥ 8 years) have shown different effects for boys and girls [5,31,32]. However, less is known about potential effect modification by child’s sex in younger children [28,33].…”
Section: Methodsmentioning
confidence: 99%
“…The increased prevalence of childhood overweight has been previously attributed to reductions in physical activity and increases in sedentary behaviors among children [4,5]. Television viewing especially is highly prevalent among young children [6], and both cross-sectional and longitudinal studies support the association between children’s television viewing time and overweight [7].…”
Section: Introductionmentioning
confidence: 99%